2011
DOI: 10.1007/s10562-011-0706-z
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Tethered Half-Titanocene Complex on Syndiotactic Poly(styrene-co-p-methylstyrene) for Using in Syndiospecific Polymerization of Styrene

Abstract: In this work the syndiotactic polystyrene copolymer, poly (styrene-co-p-methylstyrene) was prepared by the copolymerization of styrene and p-methylstyrene with cyclopentadienyltitanium trichloride/methylaluminoxane catalyst. This copolymer was functionalized with silylhydride groups. The structure of copolymer and functionalized copolymer were characterized by FT-IR, 1 H-NMR and 13 C-NMR spectroscopy. The obtained results revealed that the functionalization reaction successfully proceeds at low temperatures. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Each signal of the N/MeS copolymer was assigned as follows in reference to those of the N/S copolymer23 and S/MeS copolymer obtained by an titanium‐based catalyst26: 142.7 ppm for C 1 , 127.3 ppm for C 2 , 128.5 ppm for C 3 , 134.1 for C 4 , 21.0 for C 5 , 41.4–45.1 and 39.8 ppm for C 6 and C 7 of the MeS segment; 47.0–52.9 ppm for C 8 , 36.1–38.7 ppm for C 9 , 33.8–36 ppm for C 10 and 27.8–33.8 ppm for C 11 of the N unit. The phenyl carbons of the MeS units in the regions of 134–143 ppm and methyl carbon in the regions of 21 ppm indicate the presence of the MeS units in the N/MeS copolymer (Figure 2b).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Each signal of the N/MeS copolymer was assigned as follows in reference to those of the N/S copolymer23 and S/MeS copolymer obtained by an titanium‐based catalyst26: 142.7 ppm for C 1 , 127.3 ppm for C 2 , 128.5 ppm for C 3 , 134.1 for C 4 , 21.0 for C 5 , 41.4–45.1 and 39.8 ppm for C 6 and C 7 of the MeS segment; 47.0–52.9 ppm for C 8 , 36.1–38.7 ppm for C 9 , 33.8–36 ppm for C 10 and 27.8–33.8 ppm for C 11 of the N unit. The phenyl carbons of the MeS units in the regions of 134–143 ppm and methyl carbon in the regions of 21 ppm indicate the presence of the MeS units in the N/MeS copolymer (Figure 2b).…”
Section: Resultsmentioning
confidence: 99%
“…Typical 13 C NMR spectra of the N/MeOS, N/MeS, and N/ ClS copolymers (Run 2, 9, and 18) are shown in Figures 1b, 2b, and 3b. Each signal of the N/MeOS copolymer was assigned as follows in reference to those of N/S copolymer obtained by the same catalyst [23] and S/MeOS copolymer obtained by an yttrium-based catalyst [24,25] : 137.0 ppm for C 1 , 112.9 ppm for C 2 , 128.1 ppm for C 3 , 157.5 for C 4 , 54.9 for C 5 , 47.0 and 39.3 ppm for C 6 and C 7 of the MeOS segment; 49-52.7 ppm for C 8 , 36.5-38.8 ppm for C 9 , 33.8-36 ppm for C 10 , and 28.0-31.9 ppm for C 11 Each signal of the N/MeS copolymer was assigned as follows in reference to those of the N/S copolymer [23] and S/MeS copolymer obtained by an titanium-based catalyst [26] : 142.7 ppm for C 1 , 127.3 ppm for C 2 , 128.5 ppm for C 3 , 134.1 for C 4 , 21.0 for C 5 , 41.4-45.1 and 39.8 ppm for C 6 and C 7 of the MeS segment; 47.0-52.9 ppm for C 8 , 36.1-38.7 ppm for C 9 , 33.8-36 ppm for C 10 Each signal of N/ClS copolymer was assigned as follows in reference to those of the N/S copolymer [23] and S/ClS copoly mer obtained by a scandium-based catalyst [27] : 136.7 ppm and 135 ppm for C 1 , 126.7 ppm for C 3 , 128.4 ppm for C 2 , 131.9 for C 4 , 40.7-44.5 and 38.0 ppm for C 5 and C 6 of the ClS segment; 46.5-52.7 ppm for C 7 , 35.8-37.7 ppm for C 8 The incorporation of XS did not significantly depend on the Ni complex and decreased in the following order, MeOS ≥ MeS > S ≥ ClS. The incorporation of XS increased with lowering the polymerization temperature.…”
Section: Structures Of N/xs Copolymersmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to transition metals, rare-earth metals possess unique chemical and physical properties. In particular, rare-earth metals usually adopt the stable 3+ oxidation state. , It is noteworthy that rare-earth metal complexes have attracted much attention in the syndiospecific polymerization of styrene since 2004, in which Carpentier and Hou independently reported that the neutral ansa -neodymocene allyl complex [Flu-CMe 2 -Cp]­Nd­(C 3 H 5 )­(THF) and the cationic half-sandwich scandium alkyl catalyst system [(C 5 Me 4 SiMe 3 )­Sc­(CH 2 SiMe 3 ) (THF)]/[Ph 3 C]­[B­(C 6 F 5 ) 4 ] were highly active for the syndiospecific polymerization of styrene. , Due to the unique polymerization performance of rare-earth metal complexes in styrene polymerization, since then, extensive efforts have also been made to explore rare-earth metal catalyst systems for the syndiospecific copolymerization of styrene with ethylene or nonpolar monomers to overcome the drawbacks of sPS. In contrast, the coordination copolymerization of styrene with polar monomers remains a major challenging task because the commonly used catalysts are extremely sensitive to polar groups, which will lead to the loss of activity and selectivity, low insertion of polar monomers, and low molecular weight. …”
Section: Introductionmentioning
confidence: 99%